Evaluation of a modified salt-out method for DNA extraction from whole blood lymphocytes: A simple and economical method for gene polymorphism - mohammad shokrzadeh; Abbas Mohammadpour (Mazandaran University of Medical Sciences, 2018)
Extraction of high-quality and-quantity DNA is a fundamental requirement for genetic research. It is very important to address the use of DNA extraction methods that are simple and cost-effective in gene polymorphism with large number of samples. This study was designed to investigate the optimal DNA extraction from lymphocytic cells by salt-out method. In this study, 200 blood samples of the two groups of patients and control were collected and transferred to Ethylenediaminetetraacetic acid-containing tubes. Afterwards, DNA was extracted from 1 ml of blood cells by modified salt-out method. Furthermore three parameters in this research were evaluated, including quality (optimal density at 260 nm), quantity (DNA concentration) by electrophoresis, and efficiency of extracted DNA or polymerase chain reaction (PCR) status.The findings revealed that extracted DNA had excellent concentration and purity. The obtained results of electrophoresis confirmed the absence of any fragments in the extracted DNA. The PCR of the extracted DNA were successful, indicating lack of inhibitors in the reaction. According to the results of this study, this modified method can be used as a simple, efficient, and economical method for DNA extraction.